PERTUMBUHAN TINGGI DAN DIAMETER SERTA VOLUME TANAMAN SENGON (PARASERIANTHES FALCATARIA) UMUR 10 TAHUN DI DESA PERDANA, KECAMATAN KEMBANG JANGGUT., KUTAI KARTANEGARA - Serli Aldafiana; Agustina Murniyati (Jurnal Eboni, 2021)
Sengon (Paraserianthes falcataria) is a plant that can grow in a wide climate distribution, but is easier to grow in the tropics. This plant has a high viability because of the root culture that plunges into and widens to the side. Even between the size of the stem and the size of the roots are almost balanced. The broad and deep root reach that causes sengon (Paraserianthes falcataria) to have a high vitality. Sengon (Paraserianthes falcataria) has a taproot. The stem is round without buttresses. The purpose of this study was to determine the average height and average diameter of sengon (Paraserianthes falcataria) trees (Paraserianthes falcataria) aged 10 years. The expected results of this research as input for the development of sengon (Paraserianthes falcataria)trees in Desa Perdana, Kecamatan Kembang Janggut, Kabupaten Kutai Kartanegara. The research method used is census namely the measurement technique carried out as a whole or 100% measurement (full enumeration). The results of measurements and calculations for the diameter, height and volume of sengon (Paraserianthes falcataria) plants aged 10 years with a spacing of 3 mx 3 m as many as 424 trees with an area of 4,000 m2 in Desa Perdana, Kecamatan Kembang Janggut, obtained the following results: minimum diameter value of 7 ,9 cm, the maximum value diameter is 27 cm and the average diameter is 17,32 cm, the standard deviation is 3,67 cm and the coefficient of variation is 21,23%, while the minimum value is 10,00 m, the maximum value is 26,32 m, and the average height is 16,78 m, the standard deviation is 2,46 m and the coefficient of variation is 14,68%, minimum volume value of 0,063 m3, the maximum value volume is 0,96m3 and the average volume is 0,299 m, the standard deviation is 0,15 m3 and the coefficient of variation is 50,29%,